Dynamics in numbers of group-roosting individuals in relation to pair-sleeping occurrence and onset of egg-laying in european bee-eaters Merops apiaster - Pârâu, Liviu G. (Journal für Ornithologie, 2017)
Sleeping in the nest at the beginning of the breeding season is common for birds nesting in cavities. Here, we report evidence that European Bee-eaters Merops apiaster sleep in pairs in the nesting burrow. In 3.2% of the nest checks, we found two individuals sleeping together. This behaviour ceased once hatching started. A decrease in the number of birds at a communal roost coincided with the incidences of pair-sleeping and initiation of egg-laying. Thus, checking the burrows of European Bee-eaters at the beginning of the breeding season increases the chance of observing pair-sleeping.